The Association Between Mental Workload and Nonspecific Chronic Low Back Pain Among Operators of An On Shore Oil And Gas Company In South Sumatera - Artanto, Ardi; Wibowo, Suryo; Adi, Nuri Purwito (Occupational and Environmental Medicine Journal of Indonesia, 2024)
Background: Work location influences the proportion of operators with low back pain (LBP) at a South Sumatera onshore oil and gas company. This study aimed to determine the prevalence of nonspecific chronic LBP among the company's operators, as well as the association between quantitative and qualitative mental workload and nonspecific chronic LBP. Methods: This study was cross-sectional in design, with 96 samples collected through purposive sampling. Questionnaires and physical examinations were used to collect data. Results: Nonspecific chronic LBP was found in 32.3 percent of people. According to the multivariate analysis, moderate-heavy qualitative mental workload (OR: 5.14; 95 percent CI: 1.49-17.78), being overweight (OR 9.02 95 percent CI 2.46-33.08), being a moderate-heavy smoker (OR 4.28 95 percent CI 1.29-14.26), and sitting for more than 4 hours (OR 3.61 95 percent CI 1.13-11.52) were all associated with an increased risk of having nonspecific chronic LBP. Conclusion: Nonspecific chronic LBP is common among company operators. Individual factors associated with this finding include being overweight and smoking, while occupational factors include having a moderate-heavy qualitative mental workload and long static sitting for more than 4 hours.